Happy Jack Uraninite: A New Reference Material for High Spatial Resolution Analysis of U‐Rich Matrices. Issue 1 (19th September 2019) - Dorais, Corinne; Simonetti, Antonio; Corcoran, Loretta; Spano, Tyler L.; Burns, Peter C.
Abstract : There is currently a lack of well‐characterised matrix‐matched reference materials (RMs) for forensic analysis of U‐rich materials at high spatial resolution. This study reports a detailed characterisation of uraninite (nominally UO2+x ) from the Happy Jack Mine (UT, USA). The Happy Jack uraninite can be used as a RM for the determination of rare earth element (REE) mass fractions in nuclear materials, which provide critical information for source attribution purposes. This investigation includes powder X‐ray diffraction (pXRD) data, as well as major, minor and trace element abundances determined using a variety of micro‐analytical techniques. The chemical signature of the uraninite was investigated at the macro (cm)‐scale with micro‐X‐ray fluorescence (µXRF) mapping and at high spatial resolution (tens of micrometre scale) using electron probe microanalysis (EPMA) and laser ablation‐inductively coupled plasma‐mass spectrometry (LA‐ICP‐MS) analyses. Based on EPMA results, the uraninite is characterised by homogeneous UO2 and CaO contents of 91.57 ± 1.49% m / m (2 s uncertainty) and 2.70 ± 0.38% m / m (2 s ), respectively. Therefore, CaO abundances were used as the internal standard when conducting LA‐ICP‐MS analyses. Overall, the major element and REE compositions are homogeneous at both the centimetre and micrometre scales, allowing this material to be used as a RM for high spatial resolution analysis of U‐rich samples. Key Points: A uraninite has been characterised for use as a reference material for LA‐ICP‐MS measurement of REEs in U‐rich samples. The uraninite is characterised by homogeneous UO2 and CaO contents, the latter of which can be used as an internal standard during in situ analysis. The uraninite is available for distribution to interested laboratories.